Transition, Connection, Disconnection, and Social Media: Examining the Digital Lived Experiences of Transgender Individuals. Issue Volume 11:Issues 2(2017) (3rd April 2017) - Cannon, Yuliya; Speedlin, Stacy; Avera, Joe; Robertson, Derek; Ingram, Mercedes; Prado, Ashely
ABSTRACT: In light of persistent discrimination, many individuals who are transgender lack a safe space to connect with others. Social media has become a platform for establishing social ties, receiving education, and sharing of resources that may not otherwise be available to individuals on the margins of society. Yet little is understood about the role of social media in the lives of individuals who are transgender. In this qualitative study, the researchers examined the experiences of adults who are transgender ( N = 5) who use social media. The current study also explored possible benefits and hindrances of social media for individuals who are transgender. Two main themes emerged: social media as a resource and a path to self and authenticity. The researchers encourage counselors to become familiar with various social networking sites and their privacy settings, and propose using a theoretical framework to guide counseling work with individuals who are transgender to reflect on social media connections and disconnections.